The help - Stockett, Kathryn (Amy Einhorn Books, 2009)
In Jackson, Mississippi, in 1962, there are lines that are not crossed. With the civil rights movement exploding all around them, three women start a movement of their own, forever changing a town and the way women--black and white, mothers and daughters--view one another.